The Pakistan Paradox : Instability and Resilience - Jaffrelot, Christophe; Translator by Schoch, Cynthia (India Randam House, 2015)
Examines the history of Pakistan from its creation by elite Urdo-speaking Muslims who sought to maintain their dominance to the current rise of Islamists and ethnic separatists
Include Index
Keywords: Pakistan -- Politics and government